The Value of Rifai`Yah's Struggle in Searching for His Legality amid the Polemic on Accusations of Heresy, Pekalongan Regency 1965-1999 as a History Lesson - Ulya, Risma Sofiatil (Universitas Negeri Semarang, 2017)
This study aimed to (1) determine how the form of rifa'iyah called heretical teachings. (2) knowing the polemical form between the Jama`ah Rifa`iyah and the community. (3) Jama`ah Rifa`iyah attempts to get themselves legality. The research method used is historical, through heuristic measures, source criticism, interpretation, and writing of history or historiography. The results obtained conclusion is that Rifa`iyah teachings focus on the perfection of worship, which has been largely ignored by the public at large. Five Pillars of Islam is the belief of the creed as a differentiator between Muslims and infidels, does not mean leaving the four other pillars of prayer, alm s , fastin , pilgrimage. The misunderstanding, which led to charges of heresy. (2) Jama`ah Rifa`iyah gets Nahdliyin terror of the physical and psychological as well as a ban from Central Java High Court. (3) Approaching the ruling political class, open to the scientific study of the Rifa `iyah and actively disseminating the teachings of the Rifa `iyah .